TET-TDG Active DNA Demethylation at CpG and Non-CpG Sites. Issue 8 (16th April 2021) - DeNizio, Jamie E.; Dow, Blaine J.; Serrano, Juan C.; Ghanty, Uday; Drohat, Alexander C.; Kohli, Rahul M.
Graphical abstract: Highlights: Systematic study of all possible TET/TDG substrates in CG or non-CG contexts. Uncovers relative tolerance to CH contexts for hmC oxidation by TET. Uncovers unexpected tolerance to CH contexts for fC/caC excision by TDG. Establishes the proficiency of non-CG DNA demethylation. Provides a biochemical rationale for hmCH depletion in mCH rich genomes. Abstract: In mammalian genomes, cytosine methylation occurs predominantly at CG (or CpG) dinucleotide contexts. As part of dynamic epigenetic regulation, 5-methylcytosine (mC) can be erased by active DNA demethylation, whereby ten-eleven translocation (TET) enzymes catalyze the stepwise oxidation of mC to 5-hydroxymethylcytosine (hmC), 5-formylcytosine (fC), and 5-carboxycytosine (caC), thymine DNA glycosylase (TDG) excises fC or caC, and base excision repair yields unmodified cytosine. In certain cell types, mC is also enriched at some non-CG (or CH) dinucleotides, however hmC is not. To provide biochemical context for the distribution of modified cytosines observed in biological systems, we systematically analyzed the activity of human TET2 and TDG for substrates in CG and CH contexts. We find that while TET2 oxidizes mC more efficiently in CG versus CH sites, this context preference can be diminished for hmC oxidation. Remarkably, TDG excision of fC and caC is only modestly dependent on CG context, contrasting its strong context dependence for thymine excision. We show that collaborative TET-TDG oxidation-excision activity is only marginally reduced for CA versus CG contexts. Our findings demonstrate that the TET-TDG-mediated demethylation pathway is not limited to CG sites and suggest a rationale for the depletion of hmCH in genomes rich in mCH.